2019
DOI: 10.1007/s00402-019-03127-5
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of total knee arthroplasty in morbidly obese patients: a systematic review of the literature

Abstract: IntroductionThe increasing prevalence of obesity has led to an increase in total knee arthroplasties (TKAs) being undertaken in patients with a higher body mass index (BMI). TKA in morbidly obese patients can be technically challenging due to numerous anatomical factors and patient co-morbidities. The long-term outcomes in this patient group are unclear. This systematic review aims to compare the long-term revision rates, functional outcomes and complication rates of TKAs in morbidly obese versus non-obese pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
103
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 42 publications
0
103
0
3
Order By: Relevance
“…Obesity is considered a risk factor for both developing knee osteoarthritis (OA) and progression requiring TKA surgery at younger age (Changulani et al 2008, Singer et al 2018. Moreover, many studies have shown that morbid obesity is associated with increased risk of revision following TKA (Springer et al 2013, Roche et al 2018, Tohidi et al 2018, Boyce et al 2019. However, most of the studies report overall risk for revision without detailing reasons for revision.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is considered a risk factor for both developing knee osteoarthritis (OA) and progression requiring TKA surgery at younger age (Changulani et al 2008, Singer et al 2018. Moreover, many studies have shown that morbid obesity is associated with increased risk of revision following TKA (Springer et al 2013, Roche et al 2018, Tohidi et al 2018, Boyce et al 2019. However, most of the studies report overall risk for revision without detailing reasons for revision.…”
mentioning
confidence: 99%
“…However, most of the studies report overall risk for revision without detailing reasons for revision. The effect of obesity on revision besides an increased risk for periprosthetic joint infection (PJI) has not been thoroughly discussed in the literature (D'Apuzzo et al 2015, Wagner et al 2016, Jung et al 2017, Roche et al 2018, Boyce et al 2019. There might be a complex relation between weight and height, and TKA outcome.…”
mentioning
confidence: 99%
“…41 Obesity is associated with a longer operation time, more postoperative complications, and higher revision rates. 42,43 It was shown by multiple studies that obesity increases the risk of PJI with odds ratios between 1.73 to 6.4. 33,44,45 Malinzak reviewed more than 6000 total joint arthroplasties and found the odds of PJI is 3.2 and 18.3 times in morbidly obese and extreme obesity patients (BMI greater 50 kg/m 2 ).…”
Section: Obesitymentioning
confidence: 99%
“…Overweight patients may be at an increased risk for anesthesia‐related complications related to airway management and medication dosing . In addition, morbidly obese patients with a body mass index greater than 40 kg/m may experience complications (eg, superficial SSI, prosthetic implant infection) more frequently than nonobese patients …”
Section: Preoperative Phase Of Carementioning
confidence: 99%